Chile: The Rise and Decline of a Student Movement - Bernasconi, Andres (International Higher Education, 2012)
Students in Chile have led a major student activist movement focusing on issues of tuition costs, debts, and higher education policy. This article analyzes the causes for the activism and what has happened to the movement in recent months.